SELF COMPASSION DAN GRATITUDE SEBAGAI PREDIKTOR LONELINESS NARAPIDANA PEREMPUAN DI LAPAS PEREMPUAN KELAS IIA MEDAN - Qisthina Aulia; Bela Fira Astriska (Polteknik Ilmu Pemasyarakatan, 2022)
Female prisoners who are serving their sentence in prison are prone to feeling lonely. Loneliness is a feeling of anxiety or depression due to a discrepancy between expectations and reality and an inability to establish and maintain relationships. These feelings made prisoners easy to get psychological effects, such as depression. This study aims to determine the role of self-compassion and gratitude towards loneliness in female prisoners at Lapas Kelas IIA Medan. Sampling carried out using a non-probability technique on 251 female prisoners. The measuring instrument in this study is Self Compassion Scale (SCS) developed by Neff (2003); The Indonesian version of the Grateful Scale developed by Listiyandini et al. (2015), and the UCLA Loneliness Scale developed by Russell (1996). Through multiple linear regression analysis, self-compassion and gratitude play a significant role as predictors of loneliness by 6.5% (p<.oo1). The three dimensions of self-compassion, namely self-kindness, common humanity, and mindfulness, also significant on loneliness. The results of this study expected to be one of the considerations for correctional institutions to help female prisoners develop self-compassion and gratitude to reduce feelings of loneliness during their prison terms.